Air Pollution and Incidence of Dementia: A Systematic Review and Meta-analysis - Abolhasani, Ehsan; Hachinski, Vladimir; Ghazaleh, Nargess; Azarpazhooh, Mahmoud Reza; Mokhber, Naghmeh; Martin, Janet (Neurology, 2023)
Studies of association between air pollution and incidence of dementia have shown discrepant results. The aim of this study was to evaluate the association between air pollution and dementia. In this systematic review and meta-analysis, PubMed, MEDLINE, EMBASE, PsycINFO, Scopus, and Web of Science were searched and updated in August 2021. Population-based cohort studies that reported on hazard ratio (HR) of dementia in association with exposure to fine particulate matter (PM ), nitrogen oxides (NO ), nitrogen dioxide (NO ), or ozone (O ) in those aged >40 years were included. Data were extracted by 2 independent investigators. The main outcome was the pooled HR for dementia per increment of pollutant, calculated using a random-effects model. Results were reported in accordance with PRISMA guidelines. The protocol was registered in PROSPERO (registration number: CRD42020219036). A total of 20 studies were included in the systematic review, and 17 provided data for the meta-analysis. The total included population was 91,391,296, with 5,521,111 (6%) being diagnosed with dementia. A total of 12, 5, 6, and 4 studies were included in the meta-analyses of PM , NO , NO , and O , respectively. The risk of dementia increased by 3% per 1 μg/m increment in PM (HR, 1.03; 95% CI [1.02-1.05]; I = 100%). The association between dementia per 10 μg/m increment in NO (HR, 1.05; 95% CI [0.99-1.13]; I = 61%), NO (HR, 1.03; 95% CI [1.00-1.07]; I = 94%), and O levels (HR, 1.01; 95% CI [0.91-1.11]; I = 82%) was less clear, although a significant association could not be ruled out, and there was high heterogeneity across studies. Existing evidence suggests a significant association between exposure to PM and incidence of dementia and nonsignificant association between dementia and NO , NO , and O exposure. However, results should be interpreted in light of the small number of studies and high heterogeneity of effects across studies.